The Effect of Financial Technology and Innovation on Financial Performance in The Digital Age - Sagala, Indri Yani Agustia; Sihite, Margareth; Napitupulu, Melani (Asosiasi Dosen Akuntansi Indonesia, 2023)
This study investigates the impact of financial technology and innovation on companies' financial performance during digital transformation. As digitalization reshapes the financial industry, understanding the role of financial technology and innovation is crucial for effective financial management. The research employs a theoretical framework integrating concepts of financial technology, innovation, and financial performance. Focused on the digital era, the study utilizes Partial Least Squares Structural Equation Modeling (PLS-SEM) through the G-Form approach to establish a positive and significant influence of technological developments and innovation on performance. The findings underscore the vital contribution of adopting financial technology and innovation to enhance financial performance in the digital era. The research offers valuable insights for companies and decision-makers, providing evidence-based guidance amid the dynamic digital landscape. The results affirm that comprehending the impact of financial technology and innovation on financial performance enables the design of more effective strategies to optimize outcomes in the digital business environment. In conclusion, the study emphasizes the pivotal role of financial technology and innovation in elevating company financial performance during the digital era. It deepens our understanding of how companies can strategically leverage these advancements to achieve financial success. The research contributes to a nuanced comprehension of the intricate relationship between financial technology, innovation, and company financial performance, offering a roadmap for navigating the challenges and opportunities presented by digital transformation